Ribosomes translocation into the spore of Bacillus subtilis is highly organised and requires peptidoglycan rearrangements - Olga Iwańska; Przemysław Latoch; Mariia Kovalenko; Małgorzata Lichocka; Joanna Hołówka; Remigiusz Serwa; Agata Grzybowska; Jolanta Zakrzewska-Czerwińska; Agata L. Starosta (Nature Communications)
Abstract In the spore-forming bacterium Bacillus subtilis transcription and translation are uncoupled and the translational machinery is located at the cell poles. During sporulation, the cell undergoes morphological changes including asymmetric division and chromosome translocation into the forespore. However, the fate of translational machinery during sporulation has not been described. Here, using microscopy and mass spectrometry, we show the localisation of ribosomes during sporulation in wild type and mutant Bacillus subtilis. We demonstrate that ribosomes are associated with the asymmetric septum, a functionally important organelle in the cell’s developmental control, and that SpoIIDMP-driven peptidoglycan rearrangement is crucial for ribosomes packing into the forespore. We also show that the SpoIIIA-SpoIIQ ‘feeding-tube’ channel is not required for ribosome translocation. Our results demonstrate that translation and translational machinery are temporally and spatially organised in B. subtilis during sporulation and that the forespore ‘inherits’ ribosomes from the mother cell. We propose that the movement of ribosomes in the cell may be mediated by the bacterial homologs of cytoskeletal proteins and that the cues for asymmetric division localisation may be translation-dependent. We anticipate our findings to elicit more sophisticated structural and mechanistic studies of ribosome organisation during bacterial cell development.